3D Displacement Measurement by White Light Digital Image Analysis in Frequency Domination Area - 计欣华 杨新伟 陈金龙 (Transactions of Tianjin University, 2008)
In this paper, white light digital image analysis in frequency domination area for measuring 3D displacement is put forward. The measuring system has the characteristics of wholefield, non-contact and omnibearing measurement. It is simple and the coherent light is not demanded. Gray images before and after deformation are recorded using two CCDs at two different shooting angles, then digitalized and analyzed by frequency domination correlation arithmetic. The 2D displacement obtained is used to formulate 3D displacement via mathematical transformation, The experimental plate is 40 mm in length, 30 mm in width and 10 mm in height. The definite displacement is given using a 3D precise adjusting frame. The 3D displacement is calculated and compared with the definite displacement. The error is 4%-11% and the availability of this method was certified. Using this method, the compression deformation of a thin-wall cylinder with 140 mm in height, 64 mm in inner diameter and 64,6 mm in external diameter, was also measured. This method is proper to measure dynamic deformation.